Pengaruh Sertifikat Bank Indonesia Syariah, Jumlah Uang Beredar Dan Inflasi Terhadap Indeks Saham Syariah Indonesia - Umu Kulsum; Ibram Pinondang Dalimunthe (Jurnal Akuntansi, 2021)
This research aims to determine the macroeconomic variables of Bank Indonesia Sharia Certificate, Amount of Money In Circulation and Inflation on Indonesia Sharia Stock Index. The object in this study is the Indonesian Sharia Stock Index from January 2014 to December 2018. The method used in this study is a multiple linear regression analysis method. From the results of the hypothesis test simultaneously (test F) of Bank Indonesia Sharia Certificate, The Amount of Money Supply and Inflation has a joint (simultaneous) effect on the Indonesian Sharia Stock Index for the period 2014-2018. Based on the partial hypothetical test results (t test) on the Syraiah Indonesia Stock Index shows that the variable Certificate of Bank Indonesia Syariah and the Amount of Money In Circulation affect the Indonesian Sharia Stock Index. Meanwhile, inflation variables have no effect on Indonesia's Sharia Stock Index.